Imagery and spatial cognition : methods, models, and cognitive assessment - Vecchi, Tomaso, 1966-; Bottini, Gabriella (Advances in consciousness research, 2006)
The relationships between perception and imagery, imagery and spatial processes, memory and action: these are the main themes of this text. The interest in experimental psychology and cognitive neuroscience on imagery and spatial cognition has remarkably increased in the last decades. Different areas of research contribute to the clarification of the multiple cognitive processes subserving spatial perception and exploration, and to the definition of the neurophysiological mechanisms underpinning these cognitive functions. The aim of this book is to provide the reader (post-graduate students as.